The evolutionary relationships of microRNAs in the regulation of glucose and lipid metabolism in human and animals - Osman Sabri Kilic; Sevgi Marakli (International Journal of Pioneering Technology and Engineering, 2023)
microRNA (miRNA) is a non-coding RNA type, regulating gene expressions at a post-transcriptional level. Changes in miRNA expressions can cause problems such as lipid metabolism disorder, cardiovascular disease, growth retardation, low birth weight and insulin resistance, etc., in human and animals. In this study, we investigated the evolutionary relationships of 14 miRNAs including hsa-miR27a-5p, hsa-miR149-3p, hsa-miR374c-5p, mmu-miR-678, mmu-miR-698-5p, hsa-miR-199a-3p, hsa-miR122-3p, hsa-miR342-3p, mmu-miR201-5p, hsa-miR429, hsa-miR370-3p, hsa-miR130a-5p, hsa-miR330-3p and hsa-miR770-5p related to different metabolic pathways including cardiovascular diseases and lipid metabolism. For this purpose, miRNAs were retrieved from miRBase database. After, Clustal Omega analyses were performed for alignment, and a phylogenetic tree was constructed via MEGA 11. Phylogenetic tree indicated that 14 miRNA sequences were clustered into four groups. One group consisted of mmu-miR-678, and the other 13 sequences were separated into three groups, revealing a close relationship among miRNAs. Findings from different studies provide a new perspective for potential miRNA-based biomarkers to detect lipid metabolism disorders, cardiovascular diseases as well as related disorders.